Analysis of Risk Factors for Drug-Resistant Tuberculosis in Kenjeran Sub-District, Surabaya City - Nikolaus Yudistira; Arief Hargono (JURNAL KESEHATAN LINGKUNGAN, 2026)
Introduction: Kenjeran Sub-district in Surabaya has a considerable number of DR-TB patients, but the local contributing factors are not well understood. This research was conducted to analyze the host and environmental risk factors related to DR-TB incidence in this region. Methods: This research was an observational analytic case-control study conducted in Kenjeran Sub-district. A total of 48 respondents were sampled, consisting of 16 DR-TB patients (cases) and 32 non-DR-TB patients (controls) in a 1:2 ratio. The data of sex, age, education, employment status, income, contact with DR-TB, Diabetes Mellitus (DM), smoking, previous treatment, treatment compliance, and occupancy density were gathered using a questionnaire and medical records. Bivariate analysis was carried out using the Chi-square or Fisher exact test. Results and Discussion: Diabetes Mellitus (DM) was the sole condition that was substantially linked to the incidence of DR-TB, according to bivariate analysis (p = 0.021; OR 5.571, 95% CI 1.476–21.024). There was no statistically significant correlation found between other risk factors such housing density, contact history, treatment adherence, and prior treatment history. Conclusion: DM was found to be a substantial major risk factor for DR-TB, fulfilling the study's primary goal. Screening and treating TB patients with diabetes mellitus should be the top priorities of control initiatives. Future studies with a bigger sample size are required to corroborate these findings because the lack of relationship with other parameters suggests methodological constraints.